1993
DOI: 10.1039/fd9939500191
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscope: a new tool for imaging crystal growth processes

Abstract: We present real-time and in situ atomic force microscope (AFM) observations of solution growth on the cleavage plane of two minerals, calcite and fluorite. Different growth behaviours are exhibited: the calcite surface grows via a layerspiral mechanism, while the fluorite surface grows via the formation of sharp asperities. The difference in behaviour of the two minerals may be linked to the lack of local charge neutrality on the fluorite surface. The growth mechanisms observed on calcite and fluorite provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 15 publications
(2 reference statements)
2
36
0
Order By: Relevance
“…The natural cleavage plane of the fluorite structure {1 1 1} (Tasker, 1979), was previously studied by scanning probe microscopy during growth (Hillner et al, 1993;Guntram and Werner, 1997;Schick et al, 2004), dissolution (Hillner et al, 1993;Guntram and Werner, 1997;Cama et al, 2010) and heating (Engelhardt et al, 2000). The observed changes on the surface during those processes include the formation of steps 0.33 nm high, corresponding to one F-Ca-F layer, and facets along {1 1 0} leading to the formation of triangular pits, which is attributed to the three fold symmetry of the {1 1 1} planes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural cleavage plane of the fluorite structure {1 1 1} (Tasker, 1979), was previously studied by scanning probe microscopy during growth (Hillner et al, 1993;Guntram and Werner, 1997;Schick et al, 2004), dissolution (Hillner et al, 1993;Guntram and Werner, 1997;Cama et al, 2010) and heating (Engelhardt et al, 2000). The observed changes on the surface during those processes include the formation of steps 0.33 nm high, corresponding to one F-Ca-F layer, and facets along {1 1 0} leading to the formation of triangular pits, which is attributed to the three fold symmetry of the {1 1 1} planes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental studies of topography changes during dissolution are mainly based on 3D information obtained by atomic force microscopy (AFM) (Hillner et al, 1993;Guntram and Werner, 1997) or more recently using vertical scanning interferometry (Lü ttge et al, 1999;Cama et al, 2010). The recently developed 3-D confocal profilometry (CP) technique with nanometer scale resolution and larger scanning areas opens new possibilities to analyze rougher and steeper surfaces, which allows the study of micro-scale roughness, grain boundaries and pores, on spent nuclear fuel and geological relevant microstructures during dissolution (Godinho et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…AFM has been widely used in recent years for the study of both the in situ growth and dissolution of mineral surfaces. It has been reported that the growth of calcite from a supersaturated solution is a second-order surface controlled reaction [8][9][10]14].…”
Section: Introductionmentioning
confidence: 99%
“…So far, Hillner et al imaged crystal growth of a fluorite(111) surface in supersaturated solution by contact-mode AFM [79]. They reported the vertical growth of sharp asperities with a height of 10-500 nm on a flat terrace.…”
Section: Caf 2 (111) Surfacementioning
confidence: 99%